Gen Z's View on Islam and People's Welfare - Hanifah, Khansa; Sobri, Muhammad (Indonesian Journal of Islamic Education and Local Culture, 2024)
This research aims to provide comprehensive insights to policymakers, educators, and religious communities. This research uses a qualitative approach method with a literature review. The results of this research show that Generation Z's views on Islam in the 13-26 year age range are influenced by various factors, including the environment, media, and personal experience. It is essential to acknowledge this diversity of views and encourage open dialogue and mutual understanding among members of Generation Z to understand and respect differences. Through a literature review, I analyze Generation Z's religious perceptions, knowledge, and practices and their impact on individual and societal well-being.  My results reveal the complexity of the interactions between religious values, social values, and personal aspirations in shaping Gen Z's perspective on Islam and the well-being of the Ummah, providing important insights for further understanding religious dynamics in the digital and globalization era.